The effect of endoscopic sinus surgery on quality of life: a prospective clinical study - Sayar, Zeynep; Haksever, Mehmet; Akduman, Davut; Aslan, Sundus; Solmaz, Fevzi; Kaygusuz, Ahmet (The European Research Journal, 2015)
Objective. Chronic rhinosinusitis has a negative effect on quality of life of millions of involved patients. The aim of this study was to assess the effect of endoscopic sinus surgery on the quality of life in patients with chronic rhinosinusitis. Material and Methods. Twenty-five cases with chronic rhinosinusitis, which were resistant to 12 weeks medical treatment, have undergone Endoscopic Sinus Surgery. Two kinds of health related quality of life (HRQoL) surveys (Chronic Sinusitis Survey, Rhinosinusitis Disability Index) were applied to all cases before and at least 6 months after at the operation. Lund-Kennedy endoscopic scoring system was used as an objective evaluation. All analysis was performed using SPSS statistical software. Results. Statistically significant improvements were computed for cases before and after surgery regarding the Chronic Sinusitis Survey symptom scores (p<0.05). Also Statistically significant improvements were found for cases regarding the Rhinosinusitis Disability Index. But mean changes in endoscopic scores did not statistically correlate with changes in quality of life (p>0.05). Conlusions. Our results showed that endoscopic sinus surgery improves quality of life in cases with chronic rhinosinusitis. But this improvement did not correlate with the endoscopic scores of paranasal sinuses.